The wild birds - Strelow, Emily (Los Angeles, Calif. : A Rare Bird Book, 2020)
"Cast adrift in 1870s San Francisco after the death of her mother, a girl named Olive disguises herself as a boy and works as a lighthouse keeper's assistant on the Farallon Islands to escape the dangers of a world unkind to young women. In 1941, nomad Victor scours the Sierras searching for refuge from a home to which he never belonged. And in the present day, precocious fifteen year-old Lily struggles, despite her willfulness, to find a place for herself amongst the small town attitudes of Burning Hills, Oregon."--Jacket.
Keywords: Mothers and daughters -- Fiction; Lighthouse keepers -- Fiction; Families -- Fiction -- Northwest, Pacific; Northwest, Pacific -- Fiction; Coming of age fiction; Historical fiction